Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.21203/rs.2.12276/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Immune cell infiltration characteristics and related core genes in lupus nephritis: results from bioinformatic analysis

Abstract: Objects Lupus nephritis (LN) is a common complication of systemic lupus erythematosus that presents a high risk of end-stage renal disease. In the present study, we used CIBERSORT and gene set enrichment analysis (GSEA) of gene expression profiles to identify immune cell infiltration characteristics and related core genes in LN. Methods Datasets from the Gene Expression Omnibus, GSE32591 and GSE113342, were downloaded for further analysis. The GSE32591 dataset, which included 32 LN glomerular biopsy tissues an… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
(27 reference statements)
0
4
0
Order By: Relevance
“…In the current study, we screened GSE32591, GSE69438, and GSE127797 gene datasets of LN. As immune infiltration in glomeruli has been wellstudied by several groups (34,35), we set out to assess the importance of the immune microenvironment in LN tubulointerstitial lesions. One single cell sequence study reported kidney infiltrating immune cells mainly .…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, we screened GSE32591, GSE69438, and GSE127797 gene datasets of LN. As immune infiltration in glomeruli has been wellstudied by several groups (34,35), we set out to assess the importance of the immune microenvironment in LN tubulointerstitial lesions. One single cell sequence study reported kidney infiltrating immune cells mainly .…”
Section: Discussionmentioning
confidence: 99%
“…Cibersort is an online analysis tool for immunocell in ltration for a variety of diseases, including osteoarthritis, lupus nephritis, atopic dermatitis, acne and rosacea dermatitis [23][24][25][26]. At present, few studies have used the Cibersort method to study the characteristics of immune cell in ltration in tendinopathy.…”
Section: The Analysis Of Immune Cell In Ltrationmentioning
confidence: 99%
“…CIBERSORT is a computational approach that assesses the immune cell population pro les from fresh, frozen and xed specimens (18) originating from RNA-seq or microarray data, which is widely used in the analysis of the in ltration of 22 kinds of immune cells in different diseases such as osteoarthritis (19,20), ischemia-reperfusion injury in renal transplantation (21), lupus nephritis (22) and atopic dermatitis (23).…”
Section: Introductionmentioning
confidence: 99%